PEMBINAAN AKHLAK MELALUI LEMBAGA PENDIDIKAN: (Studi Kasus di SMP Negeri 1 Keumala) - Mardiana, Mardiana (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2024)
The objectives of this studi is include to find out the role of Islamic Religious Education teachers in the development of students' morals and the efforts made in the learning process in the classroom, to find out the moral development of students in terms of counseling, to find out the moral development of students in terms of the learning process of other subjects. This research method is qualitative, namely by describing the data obtained in the field. To obtain accurate and reliable data, researchers use data collection techniques through observation, interviews with teachers and students and documentation. The samples in this study were the principal, Islamic Religious Education teachers, tutoring teachers, and other subject teachers as many as six people. Among them, there are three people from the homeroom teacher and three more regular teachers and the last interview with students who were selected randomly, in order to get valid results. The results of the study show that, teachers of SMP Negeri 1 Keumala, in general have carried out moral development for students, both during the learning process in class and outside the classroom. In addition, the participation of all teachers in the moral development of students is very large, so that every student's actions can be monitored. However, along the way, there are still students who violate the rules. Therefore, it is expected that all parties, both parents, teachers, and the community pay attention so that what is expected can be implemented and achieved.